Checklist of Ichthyofaunal diversity of Nagaland, India - . Wewa-U; Ponglen Sukha; Kangkan Jyoti Sarma (Journal of Fisheries, 2025)
The present review presents a checklist with an aim to review and summarize the results of the systematic researches on the freshwater resources including various rivers and aquatic resources of the north eastern state of Nagaland, India. The need of such a review is of utmost importance as systematic status of many of the species has changed, and reorganization and updating of the published information has become essential for future ichthyofaunal studies in the state. The total confirmed fish species of the state of Nagaland comprise of 219 species belonging to 31 families. The most diverse family is Cyprinidae with 90 species (41.09%), followed by Sisoridae with 22 species (10.04%), Nemacheilidae with 16 species (7.3%), Bagridae with 11 species (5.02%) while the remaining 26 families account for rest of the species in the list. This paper will certainly help in making appropriate conservation and management planning for fisheries in all the rivers of Nagaland and would also be helpful in looking at the various degenerative reasons for population decline of fishes.